MULTIDISCIPLINARY STAFF AND A POSSIBILITY IN DEBATE: PHYSIOTHERAPY IN SCHOOL. (Fiep Bulletin - online, 2014)
Introduction: This article analyzed the educational legalityof multi-professionals of Education and Health, enabling inserting physiotherapy into schools. That would bring a multidisciplinary contribution to the school community, promoting the development of body culture of movement. The study was raised by the necessity to assist students who hold educational needs, to include them fully in society as independent citizens. The physiotherapist would contribute for the psychomotor development of the students, so they could fully develop their skills. The main goal was to verify the possibilitytohave multidisciplinary staffhelp in activities that meet the educational needs of these human beings. Methodology: This study was based on the bibliographic and documental methodology, on the laws that regulate the human beings' right for education and health and also on the teaching experience of the author, in teaching activities, research and extension at public elementary and high schools. Results and discussions: The analysis of results was done through construction process, and the interpretation of the research was done through bibliographic and documental review. The Federal Constitution (1988), Operational Directions of Public Teaching in the State of Goiás, Brazil (2010), and Decrees grant a special treatment concerning inclusive education. The study was based on the following authors:  Assmman (1998), Betti (1991), Delisa&Gans (2002), Freire (2007),Mantoan (2006), Moraes (2003), Moura (2009), Santos (2010), Souza (1996), among others. Conclusion: Despite being critical the existence of multidisciplinary staff like: psychologists, speech therapists, psycho-pedagogue, Occupational therapists, LIBRAS and BRAILE instructors and Physiotherapists, in the schools, and Laws granting that these multi-professionals of Education and Health work for students holding educational needs in the Operational Directions of Public Teaching in the State of Goiás, Brazil (2010), the physiotherapy is not yet effective in the school units.
Keywords: Multidisciplinary staff; Physiotherapy; Inclusion